Strategi Guru Mengatasi Kesulitan Belajar Siswa Pada Mata Pelajaran Bahasa Arab di Madrasah Tsanawiyah Yaspuri Kota Malang - Rozika Azizi; Anwar Sa’dullah; Mohammad Afifulloh (Vicratina : Jurnal Ilmiah Keagamaan, 2019)
This research aim to know the difficulty of the VIII class students of Madrasah Tsanawiyah Yaspuri Malang in every aspect such as reading, writing, and listening. Beside, the teachers’ efforts in solving the students’ difficulties of the VIII class students of Madrasah Tsanawiyah Yaspuri Malang. This research is qualitative research with observation cases. The subject of this research is the VIII class students and Arabic teacher of Madrasah Tsanawiyah Yaspuri Malang. This research Collect the data by using indirect observation, interview and documentation. The data analysis use triangulation with data reduction, data presentation and conclusion. The data validity investigation uses 3 techniques. Those are observation, interview and documentation. By using the various data source as like the data of the VIII class students and Arabic teacher.The conclusion of this research can be concluding that the teachers’ effort in solving students’ difficulties in learning nationality education is giving the remedial teaching. Give the enrichment activity, giving the learning motivation, evolving the good learning moral and habitual. The causes of students’ difficulties in learning nationality education have two factors. Those are internal and external factors. The internal factors which are come from the students’ individual include intelligence, interest, and exhaustion. The external factors come from out of the individual of the students’ comprise family, school, and environment. The strategy that used by the teacher in facing the students difficulties in learning nationality education determine the difficulties, giving the remedial learning continuously until the problem of the students can be solve.